Education on Inhaler Technique by Pharmacists To Improve The Quality of Life of COPD Patients: A Systematic Review and Meta-Analysis - Sarah Almira; Vincent Pratama; Muh Ronike Yunus; Anna Rozaliyani; Rani Sauriasari (Jurnal Respirologi Indonesia, 2023)
Background: This systematic review aimed to analyze the importance of education on using inhalers by pharmacists in improving quality of life, correct inhaler use steps, and medication adherence in patients with Chronic Obstructive Pulmonary Disease (COPD).Methods: The databases used to search for articles in this systematic review include Scopus, ScienceDirect, and Pubmed. The papers submitted were published between 2009 and 2022, with the most recent search being conducted in December 2022. This review included a randomized controlled trial evaluating education on inhaler use techniques by pharmacists to improve COPD patients' quality of life in inpatient and outpatient settings. This systematic review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) writing guidelines.Results: This systematic review used six articles from five different countries. The articles involved share similar characteristics so that analysis can be carried out. The total number of research subjects included was 913 subjects. Most studies show an increase in the quality of life among COPD patients who are given education on how to use inhalers by pharmacists using print or digital media. Measurements using the St. George's Respiratory Questionnaire (SGRQ) showed a decrease in scores at the 6-month and 12-month periods (-0.75 [95% CI (-1.46 - (-.005)]. Furthermore, two articles reported that education on the technique of using inhalers by pharmacists can also increase the accuracy of using inhalers, and three articles reported increasing medication adherence.Conclusion: Interventions such as education on using inhalers by pharmacists in inpatient and outpatient settings can improve the quality of life of COPD patients, the accuracy of the steps in using inhalers, and medication adherence.